ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI INTRADIALYTIC STRETCHING EXERCISE TERHADAP PENURUNAN KRAM OTOT PADA PASIEN YANG MENJALANI HEMODIALISA DI RSPAD GATOT SOEBROTO - Ani Lestari, (2023)
Chronic Kidney Disease (CKD) is an irreversible kidney function disorder with a decrease in glomerular filtration rate (GFR) <60 ml/minute. Hemodialysis is a kidney replacement therapy for patients with end-stage chronic renal failure. Hemodialysis can cause various complications, one of them is muscle cramps. Intradialytic muscle cramps are a symptom that causes discomfort due to electrolyte conflicts and several other factors. Therefore, patients with chronic renal disease who facing muscle cramps during hemodialysis can be given intradialytic stretching exercise therapy. The purpose of the nursing care providing is to determine the effectiveness of non-pharmacological adjunctive therapy of intradialytic stretching exercises to reduce muscle cramps in chronic kidney disease patients undergoing hemodialysis at the Gatot Soebroto Army Hospital. The instrument used in measuring the level of muscle cramps is the Cramp Questionaire Chart. The results obtained from the provision of nursing care with innovative interventions for 3 times in a week showed that the cramp level score was reduced 5 score from score 9 (severe cramps) to score 4 (mild cramps). In this study, it can be concluded that intradialytic stretching exercises is effective to reduce muscle cramps in chronic kidney disease patients undergoing hemodialysis.